Probing of Hardships and Their Factors of EFL Students in Constructing Text - Jhems Richard Hasan; Alvons Habibie; Adimawati Helingo (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
The objective of this study was to investigate students' hardships and their factors in creating descriptive texts. The subject of this study was the fourth semester of IAIN Sultan Amai Gorontalo's English Education Program. 39 students were involved in this study. Three types of instruments were employed to gather the data: documentation, questionnaires, and interviews. The document was used to evaluate students' proficiency in five writing-related areas. The questionnaire was designed to identify specific challenges with descriptive text composition. The purpose of the interview was to identify factors contributing to students' difficulty in writing descriptive texts. This study employed mix method. This study revealed that students had difficulty with content, organization, and mechanics. In terms of content, students struggled with constructing subject sentences (30.76%), supporting sentences (59.97%), and closing sentences (38.46%). Students had trouble repeating essential terms (28.20%), utilizing linking words (28.20%), and explaining the topic (43.58%). In technical, students experienced difficulty with punctuation (12.82%) and capitalization (20.51%). The factors of hardship were self-motivation, self-confidence, lack of reading, and lack of practice were internal issues. External influences included the chance to write, learning materials and media, and the absence of feedback in the teaching and learning process.